2022
DOI: 10.3390/s22082944
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Phosphorescent Carbon Dots for Anticounterfeiting and Information Encryption

Abstract: Room-temperature phosphorescent (RTP) carbon dots (CDs) have promising applications in bioimaging, anticounterfeiting, and information encryption owing to their long lifetimes and wide Stokes shifts. Numerous researchers are interested in developing highly bright RTP CDs using environmentally friendly and safe synthesis processes (e.g., natural raw materials and zero-pollution production pathways). In this study, we successfully synthesized RTP CDs using a hydrothermal process employing natural vitamins as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…After thermal treated with CDs, new BC covalent bonds will form between CDs and boric acid. [49,103,104,[107][108][109] Hence, the triplet excitons would be efficiently stabilized. Besides, introducing of B atom is also in favor in minifying ΔE ST .…”
Section: Small Molecular Matrixmentioning
confidence: 99%
“…After thermal treated with CDs, new BC covalent bonds will form between CDs and boric acid. [49,103,104,[107][108][109] Hence, the triplet excitons would be efficiently stabilized. Besides, introducing of B atom is also in favor in minifying ΔE ST .…”
Section: Small Molecular Matrixmentioning
confidence: 99%
“…Realizing the final application is the value of a material. 110,126,127,[144][145][146][147][148][149][150] information encryption, 113,115,118,119,121,123,128,[151][152][153][154][155][156][157][158][159][160] sensor detection, 114,124,129,130,147,[161][162][163][164][165][166][167][168][169][170][171][172][173][174] LEDs, [175][176][177][178]…”
Section: Applicationsmentioning
confidence: 99%
“…It allows significantly increased time to visualize cell states, enables speedy detection, and also facilitates bioimaging and detection. Generally speaking, the RTP material based on CDs possesses huge application prospects in the field of anti-counterfeiting, 110,126,127,144–150 information encryption, 113,115,118,119,121,123,128,151–160 sensor detection, 114,124,129,130,147,161–174 LEDs, 175–179 biological imaging, 134,180,181 logic gates, 133 fluorescent ink 112,182–184 and other fields 116,117,122,185–195 with the properties of DF, TADF, long afterglow life and adjustable afterglow color.…”
Section: Applicationsmentioning
confidence: 99%
“…Lin et al reported a CD-based material displaying phosphorescence emission with a lifetime of 456 ms by fixing CDs in a PVA matrix, where hydrogen bonds are formed from the functional groups on CDs . The early works simply relied on one single strategy to stabilize the triplets of CDs, resulting in the phosphorescence lifetime of the reported CD-based RTP materials of mostly less than 1 s, , accompanied by a phosphorescence quantum efficiency (PQE) of less than 10%. , Moreover, the current RTP CD systems are extremely sensitive to moisture, oxygen, pH, and organic solvents, leading to phosphorescence quenching, which significantly limits their potential applications . Thus, the exploration of new fabrication strategies to effectively rigidify the triplet excited states of CDs for achieving a long-lived and efficient RTP with excellent stability is highly desired.…”
Section: Introductionmentioning
confidence: 99%